Radiocarbon data of bulk organic matter in marine sediment core PS51/159-10 from the Laptev Sea, Arctic Ocean - Lin, Tsai-Wen; Grotheer, Hendrik; Mollenhauer, Gesine (In: Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732, 2025)
This datasheet includes radiocarbon measurement results of bulk organic matter from core PS51/159-10. Sediments were freeze-dried, ground, and weighed into silver boats, with sample sizes determined by TOC content to target 1 mg of organic carbon. Samples were acidified with three drops of 6 M HCl at 60 °C three times with one hour reaction time between treatments, then oven-dried overnight at 60 °C. Afterwards, acidified samples together with silver boats were folded into tin boats and converted into graphite targets using an elemental analyzer (Elementar vario Isotope) coupled to an automated graphitization system (Ionplus AG, AGE-3). Radiocarbon measurements were conducted using the MIni CArbon Dating System (MICADAS) accelerator mass spectrometer at Alfred Wegener Institute (AWI) (Mollenhauer et al., 2021).
Keywords: Arctic Ocean; F14C; Laptev Sea; Sediment core